Potential of a bacterial consortium to degrade azo dye Disperse Red 1 in a pilot scale anaerobic–aerobic reactor. Issue 5 (May 2015) - Franciscon, Elisangela; Mendonça, Danilo; Seber, Samile; Morales, Daniel Alexandre; Zocolo, Guilherme Julião; Zanoni, MariaValnice Boldrin; Grossman, Matthew James; Durrant, Lucia Regina; Freeman, Harold S.; Umbuzeiro, Gisela Aragão
Graphical abstract